Book review (AmeriQuests, 2017)
Humanizing Smuggling Facilitators: A Review of Gabriella Sanchez’s Courageous Work in Human Smuggling and Border Crossings. Routledge Studies in Criminal Justice, Borders, and Citizenship, 2014.